2019
DOI: 10.1021/acs.jchemed.9b00647
|View full text |Cite
|
Sign up to set email alerts
|

Student Individuality Impacts Use and Benefits of an Online Video Library for the Organic Chemistry Laboratory

Abstract: An online video library comprising three different types of videos was used intensively by bachelor-level students before and throughout an introductory organic chemistry laboratory course, when presented and assigned to the experiments appropriately. An empirical study (N = 103) revealed that the utilization of videos and preferences for video types depend crucially on individual student characteristics, such as gender, study course, intrinsic motivation, and the self-perception of conscientiousness. Student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
3
22
0
4
Order By: Relevance
“…In particular, students' comments suggested that they perceived the online videos were helpful for them to understand the lab, to prepare for the lab quizzes, and to perform the hands-on activities during the lab classes. Such results were also consistent with previous findings in the organic chemistry laboratory classes (Box et al, 2017;Chaytor et al, 2017;Fung, 2015;Jordan et al, 2016;Nadelson et al, 2015;Pölloth et al, 2020;Teo et al, 2014). The instructor who taught the organic chemistry laboratory course reported that students performed better in the lab after online videos were provided and assigned to them in 2018 Spring compared with the previous semester (2017 Fall) when online videos were not provided to students.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In particular, students' comments suggested that they perceived the online videos were helpful for them to understand the lab, to prepare for the lab quizzes, and to perform the hands-on activities during the lab classes. Such results were also consistent with previous findings in the organic chemistry laboratory classes (Box et al, 2017;Chaytor et al, 2017;Fung, 2015;Jordan et al, 2016;Nadelson et al, 2015;Pölloth et al, 2020;Teo et al, 2014). The instructor who taught the organic chemistry laboratory course reported that students performed better in the lab after online videos were provided and assigned to them in 2018 Spring compared with the previous semester (2017 Fall) when online videos were not provided to students.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis of 40 years of publications reported positive associations between intrinsic motivation and academic achievement with medium effect size for college-aged samples (Cerasoli et al, 2014;Taylor et al, 2014). Motivation is also important in the laboratory setting as students with higher intrinsic motivation made more use of the online videos (Pölloth et al, 2020), and the students performed significantly better on the lab final exams when they were more motivated to prepare for the lab (Pogacnik & Cigic, 2006). However, there is little work studying student motivation in the chemistry laboratory settings, although it is important to consider the affective domain, including in preparative activities .…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…61) Sowohl die Chemiedidaktik als auch die Fachchemie profitieren von einer direkten Zusammenarbeit, und das nicht nur in den erwähnten Projekten zur Öffentlichkeitsarbeit und Bildung. Ergänzend begleiten Didaktiker mit empirischer Forschung Lehrveranstaltungen, tragen dazu bei Laborpraktika zu verbessern, 83) untersuchen Seminare für Fachstudierende 84) und auch die Studieneingangsphase für Lehramts-und Fachstudierende der Chemie, um beispielsweise die Gründe für Studienabbrüche herauszufinden. 85 Aus Schule und Hochschule…”
Section: Ausblick: Mehr Verzahnungunclassified
“…The use of instant-feedback questions. The use of online video-based instruction has been widely reported in the literature (Harwood & McMahon, 1997;Law, 2019;Pölloth et al, 2019). From the perspective of cognitive load theory (Sweller et al, 1998), instructional videos are particularly valuable in STEM education because by prompting the use of both visual and auditory processors of working memory, they can reduce split attention and redundancy effects, leading to a reduction in the extraneous cognitive load associated with learning (Chen & Wu, 2015;Sweller et al, 1998).…”
Section: Modulating Student Behavior Using Affordances Of Learning Mamentioning
confidence: 99%